Effect of silver diamine fluoride activation on bond strength to root dentin - Sara Elmallah; Ahmed Abdou; Amr Rizk; Citra Kusumasari; Reem Ashraf (BMC, 2023)
Abstract Background To investigate the effect of silver diamine fluoride (SDF) application and activation on the bond strength of gutta-percha to dentin and resin bonded post to dentin. Methods Thirty-six human premolar teeth were used. The coronal part tooth was removed, and endodontic mechanical preparation was performed for all the teeth. The teeth were divided according to final rinse protocol (n = 9) as follows: Control group; no SDF application, SDF/NA; 38% SDF as a final rinse with no activation, SDF/MDA; 38% SDF as a final rinse with manual dynamic activation and SDF/US; 38% SDF as a final rinse with ultrasonic activation. Root canal obturation using lateral condensation technique followed by fiber post insertion after 48 h in the root canal after corresponding preparations. The roots were cut with a low-speed precision saw creating 2 mm thickness sections. A total of 4 sections were obtained from each tooth, 2 coronal specimens (with post) and 2 apical specimens (with Gutta percha). Each specimen was subjected to push-out bond strength test with a universal testing machine. Data were analyzed using two-way ANOVA. Results The Push-out bond strength at the apical root section was significantly higher in SDF/MDA and SDF/US groups compared to control group. While for the coronal part, all SDF treated specimen showed reduced Push-out bond strength. Conclusion SDF application as final rinse may reduce the bonding performance between fiber post and dentine. Activation with manual and ultrasonic methods improved the bond strength at the apical root section.